Visual Culture and the Fight for Visibility1. (11th November 2013) - Schroer, Markus; Schroer, Markus
Abstract The article explores the relationship between visual culture and the fight for visibility and attention in contemporary society. It draws on a concept of visual culture which not only sees the rising significance of the visual and the proliferation of images as its defining traits, but also the fact that, today, people are—to a much higher degree—both consumers as well as producers of images. Based on this definition, it is argued that in visually oriented communication and media societies, the anthropologically fundamental need for attention manifests itself as a fight for visibility which takes on the form of ever more extreme forms of public self‐display. Furthermore, a portrait of two social figures—the star and the voyeur—will serve as further analysis and description of the social trends which can be tied to the emergence of today's visual culture. The article will close by discussing attention and visibility in terms of inclusion and exclusion and by proposing an analytical model for differentiating four modes of existence in a visual culture.